A Rare Complication of a Vaginal Breech Delivery - H. C. Vergers-Spooren; J. W. de Leeuw (Hindawi Limited, 2011)
Rectal lesions without anal sphincter trauma in childbirth are only sporadically described in literature. We describe the case of a 29-year-old primigravida who delivered a child in frank breech presentation. During the second stage of labour a foot presented transanally through a rectal laceration with intact anal sphincters. The laceration was repaired immediately after delivery in theatre. Follow-up visits showed a properly cured laceration and no complaints of incontinence or foul discharge.